2012
DOI: 10.1007/s00432-012-1152-z
|View full text |Cite
|
Sign up to set email alerts
|

Escin augments the efficacy of gemcitabine through down-regulation of nuclear factor-κB and nuclear factor-κB-regulated gene products in pancreatic cancer both in vitro and in vivo

Abstract: These data suggest that escin, via inactivation of NF-κB, could potentiate the efficacy of gemcitabine in combating pancreatic cancer, which could be a novel and potentially important therapeutic approach for the treatment for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 36 publications
7
56
0
Order By: Relevance
“…This study is consistent with the earlier observations that support possible antitumorigenic effects of b-escin in in vitro and in vivo models (6)(7)(8)(9)(10). Previously, we showed that b-escin, at 250 and 500 ppm in the diet, inhibited colon carcinogen-induced preneoplastic foci in rat colon in a dose-dependent manner (6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study is consistent with the earlier observations that support possible antitumorigenic effects of b-escin in in vitro and in vivo models (6)(7)(8)(9)(10). Previously, we showed that b-escin, at 250 and 500 ppm in the diet, inhibited colon carcinogen-induced preneoplastic foci in rat colon in a dose-dependent manner (6).…”
Section: Discussionsupporting
confidence: 92%
“…Studies from our laboratory showed that b-escin inhibits the growth of colon cancer cells and inhibits chemically induced colon carcinogenesis in rats (6). In recent years, several studies have shown that b-escin possesses anticancer activity by inhibiting growth and inducing apoptosis in various human cancer cell lines derived from lung (7), pancreatic (8), and liver (9) cancers and in leukemia and multiple myeloma (10).…”
Section: Introductionmentioning
confidence: 99%
“…The viability of treated cells was determined by using the Cell Counting Kit-8 (CCK-8) Kit (Dojindo Laboratories) following the instructions outlined by the manufacturer and as previously described by us (40). Briefly, cells were plated at a density of 3 to 5 Â 10 3 cells per well with 200 mL of medium in 96-well microtiter plates.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…To determine the levels of protein expression, cell lysates were prepared and subjected to Western blot analysis as described previously (40). Briefly, cells were washed twice in PBS, sonicated in RIPA buffer and homogenized.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation